SOBRE O ENSINO/APRENDIZAGEM EM ARTES VISUAIS OU ARTE COMO EXPERIÊNCIA (Revista Apotheke, 2017)
This article presents some reflections on the concepts of Art as Experience and teaching / learning processes in Visual Arts, tangentially the art fields , Art Education and painting teaching, having as axis the methodological approach that has been researched in the study group Apotheke painting studio and the graduation classes and Graduate Studies in Visual Arts at the University of the State of Santa Catarina - UDESC .
Keywords: arts as experience; teaching/learning in visual art; art; art education